A novel method to derive formulas for computing the wet-bulb temperature from relative humidity and air temperature. (November 2018) - Lee, Chien; Wang, Yu-Jen
Highlights: Method to derive the formulas to directly compute the wet-bulb temperature. Applicable to any intended temperature range and air pressure. Derived formulas has the same level of accuracy as the iterative calculation method. Abstract: A novel and accurate analytical method to derive the formula for computing the wet-bulb temperature inversely from the relative humidity (or dewpoint temperature) and the air temperature is proposed, based on the separation of temperature variables for the psychrometric equation and the interpolation for their virtual inverse function. Computational accuracy can be adjusted by selecting the temperature range and the order of the interpolation. In this article, an example for creating the 5th-order polynomial formula for temperature range of 0–50 °C is presented; errors in the wet-bulb temperature range from −0.076 °C to 0.019 °C with a mean absolute error of 0.025 °C and root mean square error of 0.034 °C. Compared with previous works, the method in this article is easier to utilize, and the derived polynomial formulas are more efficient to calculate. Most importantly, the proposed method is more accurate than prior formulas and maintains the same level of accuracy as the iterative calculation method.